2017
DOI: 10.4103/0253-7176.211769
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Inpatient Treatment Completion among Females with Opioid Use Disorder: Findings from a Tertiary Care Drug Dependence Treatment Centre of India

Abstract: Introduction:Studies have reported that females who drop out prematurely from inpatient treatment have poor treatment outcome. However, literature from India is limited in this regard.Methods:We reviewed case records of female patients admitted with opioid use disorder at NDDTC, Ghaziabad between January 1, 2008 and December 31, 2012 to study the predictors of inpatient treatment completion among female patients with opioid use disorder in relation to their sociodemographic and clinical profile.Results:Over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The remaining studies appeared to describe AMA discharges exclusively, although the term was not always explicitly defined. In addition, 13 studies had fewer than 100 participants and may have been underpowered to detect significant differences between patients who had early discharges and those who had planned discharges [27,39,43,60,63–67,70,73,77,78]. Although all included studies described their settings as inpatient withdrawal management services, there was variability in treatment duration and services offered, with average lengths of stay ranging from 3 days to 6 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining studies appeared to describe AMA discharges exclusively, although the term was not always explicitly defined. In addition, 13 studies had fewer than 100 participants and may have been underpowered to detect significant differences between patients who had early discharges and those who had planned discharges [27,39,43,60,63–67,70,73,77,78]. Although all included studies described their settings as inpatient withdrawal management services, there was variability in treatment duration and services offered, with average lengths of stay ranging from 3 days to 6 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Although all included studies described their settings as inpatient withdrawal management services, there was variability in treatment duration and services offered, with average lengths of stay ranging from 3 days to 6 weeks. Furthermore, the patient populations varied, with nine studies including males only [17,36–38,58,63–65,71] and five studies including females only [21,35,39,50,53]. Other studies included patients with certain types of substance use disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This agrees with earlier research where unemployment has been found to be a consequence and risk factor and to predict treatment retention among women. [ 5 9 11 ] Around 60% of them hailed from urban areas and 88.5% were living in a nuclear family. Although the location of our hospital in a city might contribute urban predominance among inpatients, few research has discussed urban-rural differences in accessing treatment for SUD and utilization of SUD treatment due to rural specific challenges and barriers.…”
mentioning
confidence: 99%
“…Six Indian retrospective chart reviews among women with substance use disorders (wSUDs) reported an exponential increase in the number of women seeking SUD treatment (Dayal, Sarkar, & Balhara, 2017; Grover, Irpati, Saluja, Mattoo, & Basu, 2005; Malik et al, 2015; Nagendrappa, Mallanna, & Raj, 2018; Nebhinani, Sarkar, Gupta, Mattoo, & Basu, 2013; Srivastava, Mehndi, & Patel, 2015). The rates range from 100 women in a 33-year span (1978–011; Nebhinani et al, 2013) to 40 to 50 women in reviews spanning 1 year subsequently (Malik et al, 2015; Nagendrappa et al, 2018).…”
mentioning
confidence: 99%